Lexical processing of ambiguous words: dominance or associative strength? - Nievas, Francisco; Justicia, Fernando; Cañas, José J.; Bajo, M. Teresa (The Spanish Journal of Psychology, 2005)
Four experiments examined the role of meaning frequency (dominance) and associative strength (measured by associative norms) in the processing of ambiguous words in isolation. Participants made lexical decisions to targets words that were associates of the more frequent (dominant) or less frequent (subordinate) meaning of a homograph prime. The first two experiments investigated the role of associative strength at long SOAs (Stimulus Onset Asynchrony) (750 ms.), showing that meaning is facilitated by the targets’ associative strength and not by their dominance. The last two experiments traced the role associativestrength at short SOAs (250 ms), showing that the manipulation of the associative strength has no effect in the semantic priming. The conclusions are: on the one hand, semantic priming for homographs is due to associative strength manipulations at long SOAs. On the other hand, the manipulation of the associative strength has no effect when automatic processes (short SOAs) are engaged for homographs.